Capacidad institucional y su impacto en la gestión vial rural del GAD Provincial de Morona Santiago en el período 2020-2025. - Petsain Utitiaj, Diego Raúl (2025)
The research analyzes the factors that condition the effectiveness of the provincial government in addressing rural roads, a key component for territorial development. The general objective was to determine the impact of the institutional capacity of the Provincial Government of Morona Santiago on rural road management in the parishes of Alshi 9 de Octubre and San Vicente de Zuñac. The methodology employed a mixed, non-experimental, cross sectional approach, combining surveys of 151 users and 14 officials, semi-structured interviews with 5 key actors, and a documentary analysis of official sources from the period 2021-2024. The main results reveal that the Provincial GAD has a remarkable technical capacity and an effective vertical articulation to obtain financing; however, it operates under a reactive model focused on emergencies that sacrifices preventive maintenance. Additionally, it exhibits weak horizontal coordination with the parish GADs. The main conclusion is that the impact of institutional capacity on road results is indirect and is overshadowed by the intervention of other actors, such as the MTOP and a reactive management culture, which explains the absence of a significant statistical correlation between the perception of capacity and the public's evaluation of management.